2016
DOI: 10.1016/j.rppnen.2016.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Surgical risk evaluation of lung cancer in COPD patients – A cohort observational study

Abstract: Coexistence between pulmonary cancer and chronic obstructive pulmonary disease (COPD) is frequent and is anticipated to be lead to high worldwide mortality in the next decades. The most powerful therapeutic approach for non-small cell lung carcinoma is lung surgical resection. However, in COPD patients, this approach bears a higher mortality and morbidity risk, thus requiring an accurate pre-operatory evaluation of the surgical risk comprising a clinical and functional assessment at rest, as well as a cardiopu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In all included studies, surgical resection for NSCLC was performed. Neoadjuvant chemotherapy and/or adjuvant chemotherapy were included in five studies (13 %) (Rodrigues et al, 2016;Brunelli et al, 2009b;Villani and Busia, 2004;Villani et al, 2003;Toker et al, 2007). An association between outcome variables of pretreatment exercise tests and postoperative cardiac and pulmonary complications and/or postoperative mortality was found in 33 of the 38 studies (87 %).…”
Section: Treatment Complicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In all included studies, surgical resection for NSCLC was performed. Neoadjuvant chemotherapy and/or adjuvant chemotherapy were included in five studies (13 %) (Rodrigues et al, 2016;Brunelli et al, 2009b;Villani and Busia, 2004;Villani et al, 2003;Toker et al, 2007). An association between outcome variables of pretreatment exercise tests and postoperative cardiac and pulmonary complications and/or postoperative mortality was found in 33 of the 38 studies (87 %).…”
Section: Treatment Complicationsmentioning
confidence: 99%
“…In 20 (80 %) of the 25 studies where the CPET was used preoperatively, one or more outcomes were statistically significant associated with postoperative complications. Cycle ergometry was used in 20 studies (80 %) (Smith et al, 1984;Miyazaki et al, 2018;Brutsche et al, 2000;Fang et al, 2013;Nagamatsu et al, 2004;Richter Larsen et al, 1997;Campione et al, 2010;Pate et al, 1996;Shafiek et al, 2016;Rodrigues et al, 2016;Vargas Fajardo Mdel et al, 2014;Licker et al, 2011;Varela et al, 2009;Brunelli et al, 2009b;Villani and Busia, 2004;Villani et al, 2003;Bechard and Wetstein, 1987;Bolliger et al, 1995;Epstein et al, 1993;Holden et al, 1992), of which 16 (80 %) reported that preoperative CPET variables were associated with postoperative complications. Different CPET protocols were used, with ten different workload increment protocols.…”
Section: Cardiopulmonary Exercise Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Multivariate analysis revealed that lower BMI, reduced DLCO%, and operation time were significant predictors of PPCs in COPD patients receiving cancer resection. In cardiopulmonary exercise testing, Rodrigues and colleagues found that the cutoff value of 61% for peak oxygen uptake was a significant discriminator between COPD patients with and without complications following tumor resection [ 82 ]. With regard to surgical approach, Jeon and colleagues performed a propensity score-matched analysis and demonstrated that video-assisted thoracoscopic surgery in lung cancer patients with comorbid COPD could reduce PPCs compared with thoracotomy [ 83 ].…”
Section: Treatment For Lung Cancer With Copdmentioning
confidence: 99%
“… 20 ) Furthermore, COPD is a risk factor for pulmonary complications after pulmonary resection, 5 ) and COPD significantly increases the postoperative length of hospital stay compared to that of lung cancer patients without COPD. 21 ) The postoperative hospital stay for lung cancer patients is reported to be 4.3 days with preoperative rehabilitation and 9.7–12.2 days without preoperative rehabilitation. 8 ) In the present study, the mean postoperative hospital stay was 14.5±7.0 days, suggesting that prolonged hospitalization could make it difficult to maintain activity levels after surgery.…”
Section: Discussionmentioning
confidence: 99%